Partial Retention of Legacy Trees Protect Mycorrhizal Inoculum Potential, Biodiversity, and Soil Resources While Promoting Natural Regeneration of Interior Douglas-Fir - Simard, Suzanne W.; Roach, W. Jean; Beauregard, Jacob; Burkart, Julia; Cook, Dominique; Law, Danica; Murphy-Steed, Arianna; Schacter, Teah; Zickmantel, Aidan; Armstrong, Gaelin; Fraser, Kaya M.; Hart, Lia; et al. (Frontiers in Forests and Global Change, 2021)
Clearcutting reduces proximity to seed sources and mycorrhizal inoculum potential for regenerating seedlings. Partial retention of legacy trees and protection of refuge plants, as well as preservation of the forest floor, can maintain mycorrhizal networks that colonize germinants and improve nutrient supply. However, little is known of overstory retention levels that best protect mycorrhizal inoculum while also providing sufficient light and soil resources for seedling establishment. To quantify the effect of tree retention on seedling regeneration, refuge plant diversity, and resource availability, we compared five harvesting intensities with increasing retention of overstory trees (clearcutting (0% retention), seed tree (10% retention), 30% patch retention, 60% patch retention, and 100% retention in uncut controls) in an interior Douglas-fir-dominated forest in British Columbia. Seedling regeneration increased with proximity to legacy trees in partially cut forests, with increasing densities of interior Douglas-fir, western redcedar, grand fir and western hemlock with overstory tree retention. Clearcutting reduced cover of ectomycorrhizal refuge plants (from 80% to 5%) while promoting arbuscular mycorrhizal plants the year after harvest. Richness and diversity of shrubs, herbs and mosses declined with increasing harvesting intensity, but tree richness remained at control levels. The presence of legacy trees in all partially cut treatments mitigated these losses. Light availability declined logarithmically with increasing overstory cover and proximity to leave trees, but it still exceeded 1000 W m-2 in the clearcut, seed tree and 30% retention treatments. Increasing harvesting intensity reduced aboveground and belowground C stocks, particularly the forest floor. The loss of forest floor C, along with understory plant C and diversity with intense harvesting was likely associated with a loss of ectomycorrhizal inoculum potential. This study suggests that dispersed or aggregated retention of overstory trees where seed trees are spaced less than 15m apart will result in an optimal balance of seed source proximity, inoculum potential, and resource availability where seedling regeneration, plant biodiversity and carbon stocks are protected.